Site‐Selective In Situ Electrochemical Doping for Mn‐Rich Layered Oxide Cathode Materials in Lithium‐Ion Batteries. Issue 11 (19th December 2017) - Choi, Aram; Lim, Jungwoo; Kim, Hyung‐Jin; Jung, Sung Chul; Lim, Hyung‐Woo; Kim, Hanseul; Kwon, Mi‐Sook; Han, Young Kyu; Oh, Seung M.; Lee, Kyu Tae
Abstract: Various doped materials have been investigated to improve the structural stability of layered transition metal oxides for lithium‐ion batteries. Most doped materials are obtained through solid state methods, in which the doping of cations is not strictly site selective. This paper demonstrates, for the first time, an in situ electrochemical site‐selective doping process that selectively substitutes Li + at Li sites in Mn‐rich layered oxides with Mg 2+ . Mg 2+ cations are electrochemically intercalated into Li sites in delithiated Mn‐rich layered oxides, resulting in the formation of [Li1− x Mg y ][Mn1− z M z ]O2 (M = Co and Ni). This Mg 2+ intercalation is irreversible, leading to the favorable doping of Mg 2+ at the Li sites. More interestingly, the amount of intercalated Mg 2+ dopants increases with the increasing amount of Mn in Li1− x [Mn1− z M z ]O2, which is attributed to the fact that the Mn‐to‐O electron transfer enhances the attractive interaction between Mg 2+ dopants and electronegative O δ − atoms. Moreover, Mg 2+ at the Li sites in layered oxides suppresses cation mixing during cycling, resulting in markedly improved capacity retention over 200 cycles. The first‐principle calculations further clarify the role of Mg 2+ in reduced cation mixing during cycling. The new concept of in situ electrochemical doping provides a new avenue for the development of various selectively doped materials. Abstract : An in situ electrochemical site‐selective doping method selectively substitutes Li + at Li sites in Mn‐rich layered oxides with Mg 2+ . Mg 2+ is electrochemically and irreversibly intercalated into Li sites in delithiated Mn‐rich layered oxides, resulting in the formation of Mg 2+ ‐doped layered oxides. The Mg 2+ intercalation into the layered oxides strongly depends on the amount of Mn in the layered oxides.